2021
DOI: 10.1016/j.sdentj.2020.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of root conditioning agents hyaluronic acid, EDTA and chlorhexidine on the attachment of human gingival fibroblasts to healthy root surface

Abstract: Background The gold standard treatment of periodontal diseases is scaling and root planing (SRP). Different adjunctive root conditioning agents such as hyaluronic acid (HA), ethylenediaminetetraacetic acid (EDTA), and chlorhexidine (CHX) have been used with SRP to improve the smear layer removal and the healing of periodontal tissues. The aim of this study was to compare the effect of manual scaling with or without HA, EDTA, or CHX root conditioning on the attachment and viability of human gingiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The experiment concluded that hyaluronic acid decreases the friction coefficient, which proves its ability to increase lubrication between joints. In the personal care industry, Babgi et al observed the effects of applying hyaluronic acid to a healthy root surface as a conditioning agent [13]. In this study, the roots treated with HA resulted in higher cell viability compared to other samples.…”
Section: Introductionmentioning
confidence: 55%
“…The experiment concluded that hyaluronic acid decreases the friction coefficient, which proves its ability to increase lubrication between joints. In the personal care industry, Babgi et al observed the effects of applying hyaluronic acid to a healthy root surface as a conditioning agent [13]. In this study, the roots treated with HA resulted in higher cell viability compared to other samples.…”
Section: Introductionmentioning
confidence: 55%
“…High levels of tetracycline, minocycline, and doxycycline determined a dose-dependent decrease in the differentiation potential of osteoprecursor cells [ 76 ]. Chlorhexidine induced a cytotoxic effect on human periodontal cells such as gingival fibroblasts, gingival epithelial cells, periodontal ligament cells, and osteoblasts [ 77 , 78 , 79 , 80 , 81 ]. Different concentrations of sodium hypochlorite had cytotoxic effects on human periodontal ligament cells [ 79 ] and negatively affected the viability and morphology of human bone marrow mesenchymal stem cells (MSCs) [ 82 ] as well impaired the viability and proliferation of gingival MSCs [ 14 ].…”
Section: Biocompatibility Of a Sulphonic/sulfuric Acids-based Antimic...mentioning
confidence: 99%
“…Subgingival mechanical instrumentation accumulates debris onto the root surfaces, also known as the smear layer ( Figure 2 a–c), which limits the spreading of specialized cells and impairs periodontal wound healing [ 86 , 92 ]. Several adjunctive subgingivally applied agents may enhance the removal of the smear layer and stimulate the colonization of specialized cells [ 77 , 93 ], thus creating the premises for the development of a new connective tissue attachment [ 86 , 92 ]. However, some products, such as citric acid, tetracycline, or EDTA, did not provide any additional clinical benefits in an attempt to regenerate an affected periodontium [ 94 ].…”
Section: The Effect Of Sulphonic/sulfuric Acids-based Antimicrobial D...mentioning
confidence: 99%
“…Collectively, the results of previous studies have demonstrated the effective use of HA in periodontal therapy. An overview of studies using HA as a periodontal therapeutic intervention with different sample sizes and HA forms are presented in Table I (49,(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69).…”
Section: Role Of Ha and Overview Of Studies In Periodontal Therapymentioning
confidence: 99%